O discurso de ódio nazifascista no Telegram: implicações jurídicas diante dos riscos à democracia brasileira - Rosa , Isabela Quartieri da (2025)
Hyperconnectivity intensifies political polarization, disseminates misinformation, and fuels Nazi-fascist hate speech. Strategies such as the creation of common enemies and the simplification of complex problems, amplified by algorithms, undermine democracy. In this context, the present research aims to address the following issue: to what extent has the stance of Brazilian institutions contributed to the continued hosting of potential neo-Nazi hate speech content on the digital platform Telegram, originating from user posts and posing risks to human rights and democracy? To answer this question, the general objective of the research was to analyze the presence of Nazi-fascist discourse and human rights violations on the Telegram platform investigating both the platform's responsibility and the role of Brazilian institutions. The research established the following specific objectives: understanding the nature and scope of hate speech, examining the relationship between ultranationalism and neo-Nazi discourse in Brazil, identifying and analyzing neo-Nazi discourse on Telegram, assessing the legal accountability of Telegram, and analyzing the actions of Brazilian institutions in combating such discourse. The study employed a hypothetical-deductive methodology, combining theoretical elements on the formation of hate speech, the analysis of the concept of a networked society, the relationship between discourse and the shaping of identity and social opinion, and the role of ICTs in spreading extremist discourse. Through a virtual ethnographic procedure, the study analyzed the discourses present on Telegram, aiming to identify elements of hate speech and assess the risks to democracy. The research revealed that Telegram hosts content that constitutes hate speech, posing risks to Brazilian democracy, and that such content is driven by various social actors, ranging from isolated individuals to groups and organizations. The main hypothesis confirmed by the study was that posts in the analyzed group predominantly constitute Nazi-fascist hate speech, representing a real threat to democracy, and that the actions of Brazilian institutions are insufficient to curb its dissemination. The research also found that hate speech is mostly expressed in an indirect manner and that Telegram’s structure facilitates the persistence of such discourse. Regarding legal accountability, the study confirmed the hypothesis that the self-regulation of digital platforms is insufficient, highlighting the need to enhance legal accountability mechanisms. Concerning the role of Brazilian institutions, the research found that, although regulatory frameworks exist, institutional actions are inadequate and ineffective in addressing the complexity of the problem. Additionally, the study identified the vulnerability of online platform users to misinformation, which is exploited by actors with economic power to spread hate. Given this scenario, the research concludes that a more effective and coordinated response from Brazilian institutions is essential, combining prevention, repression, and education. The legal accountability of digital platforms is also deemed crucial for building a safer and more democratic digital environment.